BIOSYNTHESIS OF PARMOTREMA RETICULATUM EXTRACT INTO SILVER NANOPARTICLES: INDUCES APOPTOSIS AND WOUND HEALING - Arvind Pal; Heena Tabassum; Ritesh Tiwari; Madhuri Verma; Malti Arya (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Anticancer and antioxidant properties are present in Parmotrema reticulatum. It includes a number of bioactive compounds, including usnic acid, which has been demonstrated in multiple animal models to hasten collagen deposition, angiogenesis, and reepithelialization during wound healing. Here, we demonstrate a simple, one-step biosynthesis of silver nanoparticles using chitosan as a capping agent and hydro-alcoholic extracts of Parmotrema reticulatum as a reducing agent. The creation of silver nanoparticles (SNPs) was determined using UV-VIS spectroscopy. Smaller, less aggregated, irregular-shaped SNPs were seen, according to the SEM analysis. PC-SNPs PC-SNPs (50 mM) performed better than all other treatments, according to the MTT test, displayed IC50 value of 62.07±9.1 and 56.11±4.2 at 24 and 48 hrs, respectively. KB-3-1 cells treated with optimized PC-SNPs (50 mM) at sub IC50 and IC50 values of 65.86 µg/ml and 34 µg/ml indicates apoptotic cells with nuclear chromatin condensation and the formation of nuclear fragments and apoptotic bodies. Furthermore, the KB-3-1 oral cell line was used in a scratch experiment to test the PC-SNPs' efficiency in promoting wound healing. It was found that after receiving the PC-SNPs treatment, the KB-3-1 cell line travelled more readily towards the artificial wound. The amount of ROS was found to have greatly decreased. All of the research results pointed to Parmotrema reticulatum loaded silver nanoparticles as a potential drug delivery method with anti-proliferative and wound-healing properties.